V-SHAPED EXPORT RECOVERY: PENGARUH VARIABEL MAKROEKONOMI TERHADAP EKSPOR JAWA TIMUR SELAMA PANDEMI COVID-19 - Panjaitan, Makmur Tradesman Hasudungan; Hadi, Mohammad Sofyan; Sari, Sajida; Fithriyah, Fithriyah (Buletin Studi Ekonomi, 2021)
This study aims to (1) analyze the condition of East Java's exports during the Covid-19 pandemic; and (2) analyze whether the variable exchange rate, interest rate, and international trade price index simultaneously and partially affect East Java's exports during the Covid-19 pandemic. The data source used in this study is secondary data obtained from several government and non-government institutions such as the Central Statistics Agency (BPS), Bank of Indonesia (BI), and the Indonesian Ministry of Trade (Kemendag). The data analysis technique used in this research is static panel data regression using East Java's exports to the 13 main export destination countries of East Java. The results of this study indicate that the variable exchange rate and international trade price index (IHPI) have a significant effect both partially and simultaneously on East Java exports. Meanwhile, the interest rate variable has a simultaneous significant effect on East Java exports. Based on the results, policy policies are expected to maintain the exchange rate and the IHPI to an appropriate level.